Ecological investment funds in German-speaking Europe - Dziawgo, Leszek (Ekologiczne fundusze inwestycyjne w Niemczech, Austrii, Szwajcarii i Luksemburgu, 2019)
The aim of the article is to present and analyze fundamental data concerning the market of ecological investment funds (EIF) in German-speaking Europe (GSE) to assess the current state and prospects for this market. The hypothesis in the paper is formulated as follows: “The ecological investment funds market has been developing dynamically in the GSE region”. In the research paper, critical aspects of the functioning of socially responsible investment (SRI), both theoretical and practical, were also presented as well. The following research methods were used: critical analysis of the literature, desk research, descriptive, comparative methods and deduction method. The results prove the above-mentioned hypothesis. The primary conclusion from the research is that further development of the described market is to be expected. It was also hinted that achievements in the ecological evolution of the financial markets could become the inspiration for the financial market in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 43-52
Keywords: financial market; sustainable finance; responsible investment; ecological investment funds; rynek finansowy; zrównoważone finanse; odpowiedzialne inwestowanie; ekologiczne fundusze inwestycyjne